Assessing the reliability of FTIR spectroscopy measurements and validity of bioelectrical impedance analysis as a surrogate measure of body composition among children and adolescents aged 8-19 years attending schools in Kampala, Uganda - Catherine T. Ndagire; John H. Muyonga; Dan Isabirye; Benard Odur; Serge M. A. Somda; Richard Bukenya; Juan E. Andrade; Dorothy Nakimbugwe (BMC, 2018)
Abstract Background Accurate measurement of body composition in children and adolescents is important as the quantities of fat and fat-free mass have implications for health risk. The objectives of the present study were: to determine the reliability of Fourier Transform Infrared spectroscopy (FTIR) measurements and; compare the Fat Mass (FM), Fat Free Mass (FFM) and body fat percentage (%BF) values determined by bioelectrical impedance analysis (BIA) to those determined by deuterium dilution method (DDM) to identify correlations and agreement between the two methods. Methods A cross-sectional study was conducted among 203 children and adolescents aged 8-19 years attending schools in Kampala city, Uganda. Pearson product-moment correlation at 5% significance level was considered for assessing correlations. Bland Altman analysis was used to examine the agreement between of FTIR measurements and between estimates by DDM and BIA.. Reliability of measurements was determined by Cronbach's alpha. Results There was good agreement between the in vivo D2O saliva enrichment measurements at 3 and 4 h among the studied age groups based on Bland-Altman plots. Cronbach's alpha revealed that measurements of D2O saliva enrichment had very good reliability. For children and young adolescents, DDM and BIA gave similar estimates of FFM, FM, and %BF. Among older adolescents, BIA significantly over-estimated FFM and significantly under-estimated FM and %BF compared to estimates by DDM. The correlation between FFM, FM and %BF estimates by DDM and BIA was high and significant among young and older adolescents and for FFM among children. Conclusions Reliability of the FTIR spectroscopy measurements was very good among the studied population. BIA is suitable for assessing body composition among children (8-9 years) and young adolescents (10-14 years) but not among older adolescents (15-19 years) in Uganda. The body composition measurements of older adolescents determined by DDM can be predicted using those provided by BIA using population-specific regression equations.